2018
DOI: 10.1037/scp0000165
|View full text |Cite
|
Sign up to set email alerts
|

“Unknowing” in the 21st century: Humble detachment for Christians with repetitive negative thinking.

Abstract: Drawing from several bodies of literature (i.e., transdiagnostic, Christian theology, contemplative prayer, mindfulness), the authors developed a Christian-sensitive model for understanding repetitive negative thinking. With structural equation modeling (SEM), we empirically investigated a proposed model of the relationship between Christian college students' views of God's providence, the ability to surrender to God, humble detachment, and repetitive negative thinking. Utilizing The Cloud of Unknowing as a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In agreement, of late, some authors in the psychology of religion (Knabb & Wang, 2021; Sisemore & Knabb, 2020) and indigenous psychology (Kim et al, 2006) literatures have argued for a more balanced perspective. In fact, several empirical studies have recently investigated “local,” “insider,” “bottom-up” (Kim et al, 2006) conceptualizations of psychological and spiritual processes (Knabb et al, 2018) and interventions (Knabb et al, 2017, 2020; Knabb & Vazquez, 2018) among Christian populations. Tethered to this need for more emic assessment and intervention strategies in the psychology literature, we sought to develop a short Christian Gratitude Scale (CGS) for subsequent research—both basic and applied—within Christian communities.…”
Section: Gratitude In the Psychology Literature: Etic And Emic Approa...mentioning
confidence: 99%
“…In agreement, of late, some authors in the psychology of religion (Knabb & Wang, 2021; Sisemore & Knabb, 2020) and indigenous psychology (Kim et al, 2006) literatures have argued for a more balanced perspective. In fact, several empirical studies have recently investigated “local,” “insider,” “bottom-up” (Kim et al, 2006) conceptualizations of psychological and spiritual processes (Knabb et al, 2018) and interventions (Knabb et al, 2017, 2020; Knabb & Vazquez, 2018) among Christian populations. Tethered to this need for more emic assessment and intervention strategies in the psychology literature, we sought to develop a short Christian Gratitude Scale (CGS) for subsequent research—both basic and applied—within Christian communities.…”
Section: Gratitude In the Psychology Literature: Etic And Emic Approa...mentioning
confidence: 99%
“…Likewise, MBPs have also been developed to incorporate religion, with a number being tailored to Christian clients (e.g. [38][39][40][41][42][43][44][45][46][47][48][49][50]). These Christian MBPs demonstrate that the underpinning philosophy of the mindfulness practice can find parallels in Christian practice and theology, with studies suggesting positive effects (see Garzon et al [39] for a review).…”
Section: Mindfulness and Christian Clientsmentioning
confidence: 99%
“…Similar themes are also central to the development of Christian Accommodative Mindfulness (CAM) e.g., [38][39][40]42]. CAM draws on Knabb et al's [45] identification of "humble detachment" as a key Chrstian construct that is associated with decreases in worry and rumination. This flexible ability comprises letting go of preoccupations with inner experiences and self, and pivoting to a more transcendent awareness of God's active and loving presence.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…To operationalize this Christian construct, Knabb, Vazquez, Wang, and Bates (2018) empirically examined humble detachment as a latent variable for helping to explain the link between surrendering to God and RNT. In this study, the authors first developed a Christian-sensitive theoretical model by drawing from the Cloud of Unknowing , a 14th century anonymous Christian writing that offers instructions for contemplative (i.e., apophatic ) meditation (Bangley, 2006).…”
Section: Preventative Strategies For Repetitive Negative Thinkingmentioning
confidence: 99%
“…Using structural equation modeling (SEM) to empirically confirm the proposed model among a sample of Christian college students, Knabb, Vazquez, Wang, et al (2018) found that deeply held views of God’s providential care were positively associated with the ability to surrender to God as a form of religious coping, which was negatively linked to RNT. In addition, the surrender-RNT association was mediated by Christians’ ability to “humbly detach.” Ultimately, the Knabb, Vazquez, Wang, and Bates model laid the foundation for the manualized approach (Knabb, Vazquez, Bates et al, 2018) in the current study.…”
Section: Preventative Strategies For Repetitive Negative Thinkingmentioning
confidence: 99%